Penerapan Model ASSURE dengan Media Mentimeter pada Pembelajaran Karya Ilmiah Kelas XI SMA - Ayu Malia; Ellinia Ika Gustiani; Dwi Ratih Puspitasari; Dhini Huda Chasanati; Asep Purwo Yudi Utomo; Diyamon Prasandha (CV. Aksara Global, 2023)
The educational process functions as the intellectual development and potential of students. The use of appropriate learning models or media can encourage the growth of students' enjoyment of the learning process, increasing learning motivation. This study applies the ASSURE learning model with Mentimeter media which can be accessed through each student's device. Menimeter media is used as a form of technology application in the learning process. Mentimeter can be used as an online presentation medium or presented in a quiz format to assess students' understanding of the material provided by the teacher (Zulfa & Huda, 2021). This study uses a qualitative research method with a descriptive approach method with research instruments that use test instruments and non-test instruments. The results of this study indicate that the ASSURE model with mentimeter media can be applied in learning to analyze the systematics and language of scientific work. The use of meter media in the learning process can motivate students in learning which affects the acquisition of learning outcomes.